Impact of Timing of Admission in Labour on Subsequent Outcome (Community Based Medical Journal, 2013)
To examine the effect of timing at which women admitted either in active or latent phase of spontaneous labour on subsequent outcome. This cross-sectional study was conducted at labour ward, department of Obstetrics and Gynaecology, BSMMU hospital, Dhaka, Bangladesh, from August 2007 to November 2007, where data were collected prospectively. A total of 60 women with term, singletone pregnancy, cephalic presentation with spontaneous onset of labour admitted in labour either in active or latent phase were selected for evaluation. Patients with any medical or obstetric complications, rupture of membrane, antenatally diagnosed foetal anomalies or death and with prior caesarean section were excluded from the study. Patients with cervical dilatation at less than 4cm were categorized as latent phase and were in group I. On the other hand, patients with cervical dilatation of 4 cm or more were marked as in active phase and were allocated in group II. Baseline characteristics were compared. Outcome differences were compared using chi-square(X2) test, t test, fishers exact test, A p value